A role of the TRAIL-TRAIL receptor system in the pathogenesis of diabetes - Vaccarezza, Mauro; Delbello, Giorgio; Zauli, Giorgio (Acta Biomedica Atenei Parmensis, 2007)
The TNF-a super-family of cytokines comprises structurally related proteins that play pivotal roles in regulating cell death, immune response and inflammation. A new member of the family namely Tumor necrosis factor alpha-Related Apoptosis-Inducing Ligand (TRAIL) is involved not only in apoptosis and immune regulation, but also it has a provocative role in vascular biology as reported recently. In this report we provide evidence that this new function of TRAIL may have a significance in the pathogenesis of diabetes and in particular in the vascular alterations that occur late during the natural history of the illness. Noteworthy, depending on the type of diabetes and on the disease stage,TRAIL can have a dual role, either as immune modulator as well as a regulatory molecule of the vascular wall fitness.